Bait collecting by subsistence and recreational fishers in Knysna Estuary may impact management and conservation. Issue 2 (5th July 2019) - Simon, C; du Toit, AN; Smith, MKS; Claassens, L; Smith, F; Smith, P
Abstract : To facilitate development of tailored management strategies for bait species within Knysna Estuary (South Africa), demand for bait, harvesting activity and perceptions around conservation among recreational and subsistence bait fishers were investigated. In 2015 and 2016, bait collectors were interviewed ( n = 84) and observed ( n = 167) during low tides at six sites during peak and off-peak holiday periods. Significant associations among subsistence and recreational fishers and their favoured bait species, collecting spots and method, frequency of collection, views on regulations and desired daily limit for mudprawns suggest differences that may warrant different management strategies. Furthermore, observed methods and duration of bait collecting differed according to site, suggesting spatial variation in baiting pressures. Subsistence fishers potentially collect more mudprawns more frequently than do recreational fishers and consequently have a greater impact on mudprawn populations. By contrast, recreational fishers collect more polychaete worms, but because they are mainly active during holidays, their impact on these species may be localised and not yet critical. Most subsistence fishers would like increased daily bag limits, to sell bait and would welcome a rotational zonation scheme to replace the current permanent exclusion zone. The merits and disadvantages of these management options and suggestions are discussed.